The Legal Relationship Between Merah Putih Cooperative & Village-Owned Enterprises - Andriyansyah Andriyansyah; Armansyah Armansyah; Heri Heriyanto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2026)
This study examines the legal relationship between Koperasi Merah Putih and Badan Usaha Milik Desa (BUMDes) in Indonesia’s village economic governance system. Using a normative juridical method with statutory and conceptual approaches, this study analyzes the regulatory framework, institutional overlap, and legal construction between the two entities. The findings indicate that Koperasi Merah Putih and BUMDes possess legitimate legal foundations but are governed under different legal regimes, resulting in legal uncertainty, overlapping authority, duplication of business functions, and institutional fragmentation at the village level. The study further reveals that the absence of clear regulatory coordination creates potential conflicts in village economic management. Therefore, this research proposes an ideal legal relationship model based on strategic partnership, functional differentiation, institutional coordination, regulatory harmonization, and participatory governance. This model is expected to strengthen legal certainty, prevent institutional conflicts, improve village economic governance, and support inclusive and sustainable rural economic development in Indonesia.